4.0 INDUSTRIAL REVOLUTION IN THE CONCEPT OF PANCASILA INDUSTRIAL RELATIONS AND THE DEVELOPMENT OF SKILLS AND COMPENSATION TO WORKERS - Zulkarnaen, Hunaeni (International Journal of Research -GRANTHAALAYAH, 2019)
4.0 industrial revolution gave birth to robotic technology, digital that has a massive impact on human life in the world, which encourages automation in all business or company activity processes and changes the order of almost every industry in every country. The extent of this change marks the transformation of the entire production and management system of companies in the world. In addition to the potential to improve the quality of life of the world community, it is feared that the industrial revolution 4.0 will take over human work resulting in mass layoffs. The purpose of this article is to analyze the Pancasila industrial relations, skills development and compensation to workers in the era of the industrial revolution 4.0. The method of approach used in this research is normative juridical, which is studying and studying the principles of law, especially positive legal principles derived from library research materials available from the laws and regulations as well as the provisions using the material primary and secondary law. The conclusion of this article is that companies must utilize the functions of Human Resource Management (HRM) and one of them is the function of skills development and compensation. The skill development function is the process of increasing the technical, theoretical, conceptual, and moral skills of workers through education and training, in accordance with the employment needs of the Industrial Revolution 4.0 period. Whereas the compensation function is that the company fairly and appropriately provides direct remuneration in the form of venture capital (money or goods) to workers who are forced to be laid off due to the negative impact of the company applying robotic, digital and automation technology. Fair is interpreted in accordance with the contribution of workers to the company and is feasible to be interpreted at least to meet the primary needs (clothing, housing, food) of workers and their families.